2017
DOI: 10.1159/000449081
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Therapeutic Needs: Focus on Intestinal Fibrosis Surgical Approach: Resection, Strictureplasty and Others

Abstract: Background: In patients with ileo-colonic Crohn's disease (CD), the main consequence of the development of intestinal fibrosis is the occurrence of a localized symptomatic stenosis for which treatment is mandatory. Besides medical treatment, which is still considered to be ineffective against non-inflammatory fibrotic intestinal stenosis due to CD, there are 2 options for the treatment of such stenosis: endoscopic and surgical approaches. Key Messages: Endoscopic treatment includes balloon dilatation and stent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Most patients can only rely on conservative treatment and fibrosis will remain throughout the patient's lifetime. In severe cases, fibrosis can be relieved through surgery, but patients have a high probability of recurrence ( 38 ). In view of the fact that clinical studies have reported that there are effective treatments for organ fibrosis, including lung and skin ( 39 41 ), it is a reasonable idea to similarly improve intestinal fibrosis using anti-fibrotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients can only rely on conservative treatment and fibrosis will remain throughout the patient's lifetime. In severe cases, fibrosis can be relieved through surgery, but patients have a high probability of recurrence ( 38 ). In view of the fact that clinical studies have reported that there are effective treatments for organ fibrosis, including lung and skin ( 39 41 ), it is a reasonable idea to similarly improve intestinal fibrosis using anti-fibrotic drugs.…”
Section: Discussionmentioning
confidence: 99%